The Evaluation Of The Prospect Series In Terms Of Vocabulary As The English Material Of Iran’s Junior High School - Hassanpour, Milad; EftekhariMannesh, Majid (International Journal of Psychosocial Rehabilitation, 2024)
Undoubtedly, investigating the frequency of words in Prospect series can lead to improvement of students in order to shed light on the evaluation of teaching materials in the context of Iran. It is needed to investigate the frequency of the words of Prospect series. Using the most frequent words can enhance the efficiency of students’ English vocabulary knowledge. The present study aimed at finding out the frequency of words of Prospect series as part of the Iranian junior high school. To this end, the words of Prospect series were gathered. Since, this study sought for evaluation of word frequency of vocabulary, another material was needed. Therefore, COCA online website was used. After finding their frequency, the most and the least frequent words, they were put into several tables. Based on word frequency analysis, words chosen for Prospect series are not the most frequent words for junior high school students. Therefore, the null hypothesis could be proved that the words chosen for Prospect series are not the most frequent words in English language for junior high school students in Iran. According to the result of the present study, the word selection of high school English materials is not useful enough therefore it needs revision. Finally, it can be concluded from the result of the present study, there should be more focus on material evaluation in particular English materials which have been used in junior high school level in Iran to compensate the recent shortages in terms of word selection.